A Facile Removal of Phenol in Wastewater Using Crosslinked β‐Cyclodextrin Particles with Ultrasonic Treatment. Issue 1 (1st July 2013) - Wang, Haijun; Wang, Youtao; Zhou, Yuqing; Han, Pingfang; Lü, Xiaoping
Abstract A crosslinked β‐cyclodextrin polymer (β‐CD‐MDI), synthesized by the modification of β‐cyclodextrin (β‐CD) with crosslinking reagent diphenyl methane diisocyanate (MDI), was prepared and used as an adsorbent in the treatment of phenol wastewater ultrasonic aided. An infrared spectroscopy test was conducted to characterize β‐CD‐MDI. The adsorption capacity of phenol in wastewater was determined by assessing the corresponding parameters, such as the amount of adsorbent β‐CD‐MDI, the initial concentration of phenol, the influence of pH and ultrasonic intensity. The adsorption efficiency of β‐CD‐MDI is up to 87.3% with an amount of crosslinked polymer of 40 g/L, an initial phenol concentration of 100 mg/L and a wastewater pH of 6. The application of ultrasound can facilitate the purification of wastewater and reduce the adsorption time remarkably.